Penerapan Technological Pedagogical and Content Knowledge (TPACK) dalam Pengajaran Keterampilan Berbahasa Arab - Haniefa, Rifda; Samsudin, Mohamad (STAINI Press, 2023)
The development of ICT (Information, communication, & technology requires teachers to innovate and align themselves with technological developments. The teacher's ability to apply technology in learning can be seen through the teacher's TPACK (Technological Pedagogical Content Knowledge). TPACK is a theoretical framework that integrates technology, pedagogic , and subject matter in learning. This article aims to examine the elements of TPACK and its application in learning Arabic. This research is a qualitative type of research through literature study. The research stages were carried out by collecting library sources, both primary and secondary. This study carried out classification data based on research formulas TPACK is very helpful in teaching Arabic skills, because technology can complement teaching and make teaching more meaningful and interactive The implementation of TPACK in teaching Arabic skills is different for each teacher, this is influenced by the teacher's ability to master the seven components of TPACK . The more optimal the Arabic language teacher is in exploring and adding to their abilities, knowledge, and insights regarding both Arabic and TPACK, the better the teaching will be